Heavier than heaven a biography of Kurt Cobain - Cross, Charles R. 1957- (Hyperion, 2001)
Based on extensive research, more than four hundred interviews, and Kurt Cobain's unpublished diaries, a portrait of the late rock star traces his rise to fame, his relationship with wife Courtney Love, and his tragic suicide.